Kepribadian Suami Seniwati Ketoprak dalam Novel Tabon Karya Margareth Widhy Pratiwi: Kajian Psikoanalisis C.G. Jung - Lekas Tristyesha; Teguh Supriyanto; Sucipto Hadi Purnomo (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to describe the personality of Karsana, the husband of a ketoprak actress in novel Tabon by Margareth Widhy Pratiwi, and the impact of Karsana’s psychological disturbance on his life. This study uses a qualitative approach with a literary psychology analysis method. The data source is the novel Tabon by Margareth Widhy Pratiwi. The data consists of dialogue excerpts between characters related to the husband of the ketoprak artist, as well as his dialogue with other characters and narrative sentences. The data was collected using heuristic reading techniques. The data were analyzed using the language style, point of view, and telling showing models. This study used Carl Gustav Jung's psychoanalysis theory. The results of the study show that Karsana has a personality with aspects of conscious attitude that tend to be introverted, personal unconscious, and collective unconscious in the form of shadow and persona. Regarding the impact of Karsana's psychological disturbance on his life, when he experiences conscious, Karsana is able to distinguish between right and wrong. Conversely, when he experiences personal unconscious, Karsana loses his rationality. Even when he experiences collective unconscious, Karsana no longer becomes his true self.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kepribadian Karsana yang merupakan suami seniwati ketoprak pada novel Tabon karya Margareth Widhy Partiwi dan dampak keguncangan jiwa Karsana atas kehidupannya. Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian psikologi sastra. Sumber data novel Tabon karya Margareth Widhy Pratiwi. Dengan data berupa kutipan dialog antartokoh yang berkaitan dengan tokoh suami seniwati ketoprak maupun dialog tokoh tersebut dengan tokoh lainnya dan kalimat kalimat naratif. Data dikumpulkan dengan teknik pembacaan heuristik dan dianalisis dengan model gaya bahasa, point of view, dan telling showing. Dalam penelitian ini digunakan teori psikoanalisis Carl Gustav Jung. Hasil penelitian menunjukkan bahwa pada Karsana ditemukan kepribadian dengan aspek kesadaran sikap jiwa cenderung introvert, ketidaksadaran personal, serta ketidaksadaran kolektif dengan bentuk shadow dan persona. Adapun dampak keguncangan jiwa Karsana atas kehidupannya, saat mengalami kesadaran, Karsana mampu membedakan antara benar dan salah. Sebaliknya, saat mengalami ketidaksadaran personal, Karsana kehilangan rasionalitas. Bahkan saat mengalami ketidaksadaran kolektif, Karsana tidak menjadi dirinya sendiri.